“Kissing Ovaries” and deep endometriosis: Case report with surgical outcome - Caldana, Nárima; Gabriel Costa Sousa, Íthalo; Moletto Polveiro, Isabela; Faria Sales, Suzana; Vetorasso Cabrera Mano, Valentina (Seven Editora, 2023)
Endometriosis is a chronic gynecological disease that affects about 2 to 10% of women of reproductive age (Barbara, Facchin, Buggio, et al., 2017; Hudson et al., 2016). Due to the variety and severity of symptoms, endometriosis has harmful physical, psychological, social, sexual, and professional consequences (Friedl et al., 2015; Hämmerli et al., 2018; Roomaney & Kagee, 2016). DOI: https://doi.org/10.56238/alookdevelopv1-004